Mobile virtual network operator as a new type of a telecommunication services provider - Štěpán, Marek (2012)
The primary objective of the master's thesis is to identify and to characterize following action steps, which lead to establish a virtual network operator as a new start-up company. Firstly, a virtual operator is characterized from a technical point of view and as an innovation. Czech telecommunication market is compared to foreign markets by its price level. The power of market competitors was described and market gaps were identified. A project founding a virtual network operator was made to support the main objective of the thesis. General action steps were identified and commented after the project part of the thesis.